Consensus quality indicators for monitoring multiple sclerosis - Isabel Voigt; Stefanie Fischer; Undine Proschmann; Urszula Konofalska; Peggy Richter; Hannes Schlieter; Thomas Berger; Sven G. Meuth; Hans-Peter Hartung; Katja Akgün; Tjalf Ziemssen (Elsevier, 2024)
Summary: Multiple sclerosis (MS) as a chronic, degenerative autoimmune disease of the central nervous system has a longitudinal and heterogeneous course with increasing treatment options and risk profiles requiring constant monitoring of a growing number of parameters. Despite treatment guidelines, there is a lack of strategic and individualised monitoring pathways, including respective quality indicators (QIs). To address this, we systematically developed transparent, traceable, and measurable QIs for MS monitoring. Through literature review, expert discussions, and consensus-building, existing QIs were identified and refined. In a two-stage online Delphi process involving MS specialists (on average 53 years old and with 25 years of professional experience), the QIs were evaluated for content, clarity, and intelligibility, resulting in a set of 24 QIs and checklists to assess the quality of care. The final QIs provide a structured approach to document, monitor, and enhance the quality of care for people with MS across their treatment journey.